Description of Social Well-Being in Adolescents in Orphanage Aisyiyah Sidoarjo - Mochammad Abdul Rochman Al'Ayub; Effy Wardati Maryam (Athena: Journal of Social, Culture and Society, 2025)
This study aims to determine how the description of social well-being in Aisyiyah Sidoarjo orphanage children, this study uses descriptive quantitative methods with a population of 130 people, with sampling techniques using the saturated sample method. This research instrument uses a psychological scale with a Likert model, this scale is an adoption that has been developed by previous researchers who are arranged based on aspects of social well-being, namely social acceptance, social contribution, social relationships, social integration, and social actualization. After the data was collected and processed, the results showed that social well-being in adolescents at Aisyiyah Sidoarjo orphanage was in the low category with a percentage of 40.8%, and the prominent aspect of social well-being of Aisyiyah Sidoarjo orphanage children was self-acceptance with a percentage of 56.2% and the less aspect was social relations with a percentage of 45.4%. Then when viewed from the gender of women is more dominant than men with a percentage of 37.2%, then looking at children who live outside the orphanage shows that social well-being in women is better than men with a percentage of 30.4%.